Policing a class society: New York City in the 1990s - Harring, Sidney L. (Social justice, 1999)
Part of a special issue celebrating 25 years of this journal. The writers discuss problems associated with policing New York City in the 1990s. New York academics continue to analyze the police from a 1960s and 1970s perspective. The New York City Police Department (NYPD) is still deeply entrenched in the same machine politics that has dominated New York for the past century and longer. The case concerning the rape and torture of Abner Louima in 1997 demonstrated the systematic failure of police management to address the problem of police violence, and the killing of Amadou Diallo in 1999 was the product of the NYPD's aggressive policing policy.